(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Caste system in Indian society is based on economic and social inequality. Untouchables or Scheduled Castes were denied their economic, social, political and cultural rights in various social forms. Scheduled castes have faced discrimination and social exclusion since historical times. They were placed at the lowest level in the caste hierarchy. Due to discrimination and social exclusion, the Schedules have to endure a great deal of poverty and exploitation. The government has been making continuous and sustained efforts to improve the economic and social conditions of Scheduled Castes, yet this section of the society ranks among the poorest and lowest strata of Indian society if any human development criteria is used to classify it. The deprivation of Scheduled Castes is associated with economic and social exclusion and caste-based discrimination. In this research paper, the economic and social status of scheduled castes in Maharashtra state and Nashik district has been discussed.